2021
DOI: 10.52547/rbmb.10.3.402
|View full text |Cite
|
Sign up to set email alerts
|

Using the PCR and Blood Agar in Diagnosis of Semen Bacterial Contamination of Fertile and Infertile Men

Abstract: Background: One of the causes of male infertility is Genital tract infections (GTI). Considering the importance of GTI, widespread recognition of them seems necessary. we aimed to characterize and compare semen microbial populations in fertile and infertile men who referred to an infertility clinic in Yazd, Iran. Methods: Semen samples were collected from two groups of fertile (268) and infertile (210) men. Sperm analysis (concentration, morphology, viability and motility parameters) were performed according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…• Temporary or permanent oligozoospermia to azoospermia [142] Staphylococcus aureus • Seminal vesicles and semen [127,[147][148][149][150][151][152][153][154][155][156] • Testis [157] • Prostate [125,151,158,159] • Seminal vesicle, prostatic and testicular abscesses [125,150,151,157,159,160] • Epididymo-orchitis [150,157] • Foci of prostatic and testicular necrosis [157,160] • Enlarged and tender prostate [125,150,151,158,160] • Dysuria [125,150,151,157,158] • Controversial [148,[152][153][154][155] Treponema pallidum • Semen [161,162] • Penis [162,163] • Testis [164]…”
Section: Infected Genital Organs Damage To Genital Tract Organs Cause...mentioning
confidence: 99%
See 1 more Smart Citation
“…• Temporary or permanent oligozoospermia to azoospermia [142] Staphylococcus aureus • Seminal vesicles and semen [127,[147][148][149][150][151][152][153][154][155][156] • Testis [157] • Prostate [125,151,158,159] • Seminal vesicle, prostatic and testicular abscesses [125,150,151,157,159,160] • Epididymo-orchitis [150,157] • Foci of prostatic and testicular necrosis [157,160] • Enlarged and tender prostate [125,150,151,158,160] • Dysuria [125,150,151,157,158] • Controversial [148,[152][153][154][155] Treponema pallidum • Semen [161,162] • Penis [162,163] • Testis [164]…”
Section: Infected Genital Organs Damage To Genital Tract Organs Cause...mentioning
confidence: 99%
“…In fact, the impact of S. aureus on male fertility is still controversial. Indeed, studies identified S. aureus in the semen of infertile men, sometimes in association with altered sperm parameters [148,[152][153][154] but a recent case-control study revealed that the percentages of S. aureus-positive semen samples from fertile and infertile men were not statistically different [155]. Finally, the controversy may also lay in the fact that the percentage of semen positive for S. aureus highly differs from studies and/or from countries, some showing little sperm contamination [149,155,156], others medium contamination [148,154], and even high contamination [127,147,152,153].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%